Meningkatkan Pola Berpikir Anak di Perpustakaan Menggunakan Storytelling Games - Ananda, Angelia Selma (Perpustakaan Universitas Gadjah Mada, 2023)
This research aims to determine the role of libraries in the development of children's thinking patterns by using storytelling games to explore the use of learning designed in easy and simple games so that the objects around them are effective in developing critical thinking in groups of children. The role of libraries is very much needed because libraries are institutions that are close to the community, so they can help teachers and parents in training children's thinking patterns to become critical thinking patterns using storytelling games. This research focuses on the role of libraries in children's thinking patterns by using storytelling games. Storytelling games can be a tool to improve children's thinking patterns that can be used by libraries. This research uses a qualitative approach. The research method uses the literature study method. The source and process of data collection in the literature study method is carried out by accessing information from the library, reading, taking notes and processing research materials. Data analysis is carried out through a summary of the sources that have been found. The analysis process involves data reduction, data presentation, data reduction again, and drawing conclusions from the information that has been collected. The research results show that libraries have a role in improving children's thinking patterns through storytelling games, such as adding fun, increasing imagination and enthusiasm. The method used in storytelling is a narrating method, where this requires the role of the library to increase children's enthusiasm and regulate children's emotions.